Prevalencia de Preeclampsia en el Hospital Regional de Encarnación - 2013 (Journal on studies and research of academic knowledge, 2015)
The preeclampsia is a disease of unknown and multifactorial origin. The main objective of the following study was to determine the prevalence of Pre-eclampsia in pregnant patients who came to the service of maternity of the Regional Hospital of Encarnación in the period between January to December 2013.The methodological design was descriptive observational cross sectional, retrospective type with analytical component and yielded the following results: the prevalence was 3% the perity and multiparity, a high percentage of patients referred having suffered this disease in previous pregnancies and prenatal null stood in these patients taking into account the gravity of the pathology study.
Keywords: Parity; History of preeclampsia in the previous pregnancy; preeclampsia (mild, severe); Type of delivery (vaginal or cesarean section)